2020
DOI: 10.1590/1807-1929/agriambi.v24n2p89-94
|View full text |Cite
|
Sign up to set email alerts
|

Co-inoculation with Azospirillum brasilense in soybean cultivars subjected to water déficit

Abstract: This study aimed to verify the effect of co-inoculation, association between Azospirillum brasilense and Bradyrhizobium japonicum bacteria, on soybean plants subjected to water deficit at two sowing dates. Two field experiments were conducted at the Universidade Federal de Tocantins, campus of Palmas, Brazil, in 2016. The experimental design was randomized blocks in a split-split-plot arrangement with four repetitions, where the plots consisted of two irrigation depths (100 and 25% of crop evapotranspiration -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…Zahedi & Abbasi (2015) observed that the morphological characteristics of soybean plants improved under water stress. Naoe et al (2020) also found a positive response in the yield of soybean submitted to drought. However, there is a lack of concise data for the effects of plant-bacteria interaction on the chemical composition of beans.…”
Section: Palavras-chavementioning
confidence: 80%
See 1 more Smart Citation
“…Zahedi & Abbasi (2015) observed that the morphological characteristics of soybean plants improved under water stress. Naoe et al (2020) also found a positive response in the yield of soybean submitted to drought. However, there is a lack of concise data for the effects of plant-bacteria interaction on the chemical composition of beans.…”
Section: Palavras-chavementioning
confidence: 80%
“…The double (IM x I; IM x D; C x IM) and triple (IM x I x D; C x IM x I; C x IM x D) interactions, in which the inoculation methods were considered, did not affect the oil or protein content in the beans. According to Hungria et al (2013), Zahed & Abassi (2016) and Naoe et al (2020), co-inoculation improves the soybean agronomic characteristics and yield in adverse conditions such as drought. However, in the present study, the effects of this technique for increasing the soybean oil or protein content were not verified.…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with those obtained by Barbosa et al (2011), Finoto et al (2017), and Carvalho et al (2021, who also observed the effects of high temperatures and water reductions in the increase of oil content in soybean grains. Naoe et al (2020), also had about the isolated and/or associated effect of low water availability and high temperatures on the oil content.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of lower water availability during the grain filling phase promotes changes in metabolic routes [22], reducing the number of grains per m 2 , the number of ears per m 2 [23], length of internodes, the storage capacity of sugars in the stem, in addition to resulting in thinner stems, smaller plants and smaller leaf area, which can impair the development of plants [24].…”
Section: Table 4 Estimates Of the Simple (%Fs) And Complex (%Fc) Fractions Of The Cultivar X Environments Interactionmentioning
confidence: 99%